Effectiveness and cost-effectiveness of a very brief physical activity intervention delivered in NHS Health Checks (VBI Trial): study protocol for a randomised controlled trial. Issue 1 (December 2016) - Mitchell, Joanna; Hardeman, Wendy; Pears, Sally; Vasconcelos, Joana; Prevost, A.; Wilson, Ed; Sutton, Stephen
Abstract Background Physical activity interventions that are targeted at individuals can be effective in encouraging people to be more physically active. However, most such interventions are too long or complex and not scalable to the general population. This trial will test the effectiveness and cost-effectiveness of a very brief physical activity intervention when delivered as part of preventative health checks in primary care (National Health Service (NHS) Health Check). Methods/design The Very Brief Intervention (VBI) Trial is a two parallel-group, randomised, controlled trial with 1:1 individual allocation and follow-up at 3 months. A total of 1, 140 participants will be recruited from 23 primary care practices in the east of England. Participants eligible for an NHS Health Check and who are considered suitable to take part by their doctor and able to provide written informed consent are eligible for the trial. Participants are randomly assigned at the beginning of the NHS Health Check to either 1) the control arm, in which they receive only the NHS Health Check, or 2) the intervention arm, in which they receive the NHS Health Check plus 'Step It Up' (a very brief intervention that can be delivered in 5 minutes by nurses and/or healthcare assistants at the end of the Health Check). 'Step It Up' includes (1) a face-to-face discussion, including feedback on current activity level, recommendations for physical activity, and information on how to use a pedometer, set step goals, and monitor progress; (2) written material supporting the discussion and tips and links to further resources to help increase physical activity; and (3) a pedometer to wear and a step chart for monitoring progress. The primary outcome is accelerometer counts per minute at 3-month follow-up. Secondary outcomes include the time spent in the different levels of physical activity, self-reported physical activity and economic measures. Trial recruitment is underway. Discussion The VBI trial will provide evidence on the effectiveness and cost-effectiveness of the Step It Up intervention delivered during NHS Health Checks and will inform policy decisions about introducing very brief interventions into routine primary care practice. Trial registration ISRCTN Registry, ISRCTN72691150 . Registered on 17 July 2014.